POLITIK HUKUM PENGENAAN PAJAK ATAS JASA HIBURAN DIKAITKAN DENGAN FUNGSI PAJAK - Hutabarat, Bardamean Marulitua Milko; Khalimi, Khalimi; Franciska, Wira (SINERGI : Jurnal Riset Ilmiah, 2025)
Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (HKPD Law) has granted broader authority to regional governments in determining tax objects and rates, including taxes on entertainment services. However, the imposition of high tax rates ranging from 40% to 75% for services such as discotheques, karaoke venues, nightclubs, bars, and spas has sparked debate regarding the function of taxation as both a fiscal and social instrument. This research addresses two main issues: how regional regulations are implemented in determining entertainment tax collection, and how the government’s legal politics utilize entertainment taxes as an instrument to regulate public behavior.  Legal politics theory and tax theory are applied to analyze the relationship between political configuration and the legal products of entertainment taxation, assessing to what extent these policies reflect substantive justice, flexibility, and public participation. The research employs a normative juridical legal method using statutory and conceptual approaches, complemented by a teleological approach to evaluate the alignment of entertainment tax policies with the objectives of law. The findings reveal that although the HKPD Law aims to strengthen fiscal decentralization, the implementation of entertainment tax policies in the regions has yet to reflect principles of inclusivity and social justice. Public participation and industry stakeholder involvement in the legislative process remain limited, and the imposition of 40%-75% tax rates was carried out without adequate public consultation. The regulation tends to function as social control with limited regional flexibility and minimal fiscal incentives, leading to tax avoidance and negative impacts on related business sectors. The role of regional executives is also suboptimal, as evidenced by delays in issuing local regulations (Perda) as mandated by the HKPD Law. Therefore, policy reforms are needed, including broader public consultations, flexible tariff mechanisms based on regional economic conditions, and a national evaluation system of regional tax policies, to ensure that taxation functions as a fair and proportional tool for both regional revenue generation and social control.